Glomerular Hyperfiltration in Obese African American Hypertensive Patients Is Associated With Elevated Urinary Mitochondrial-DNA Copy Number. (14th June 2017) - Eirin, Alfonso; Saad, Ahmed; Woollard, John R; Juncos, Luis A; Calhoun, David A; Tang, Hui; Lerman, Amir; Textor, Stephen C; Lerman, Lilach O
Abstract: BACKGROUND: Glomerular hyperfiltration may contribute to the high incidence of renal disease in Obese African Americans essential hypertensive (ObAAEH) patients, but the precise mechanisms responsible for renal injury have not been elucidated. Mitochondria are important determinants of renal injury in hypertension, and increased levels of mitochondrial DNA (mtDNA) in the urine may indicate renal mitochondrial injury. We hypothesized that urine mtDNA copy numbers would be higher in ObAAEH compared to Caucasian essential hypertensive (CEH) patients. METHODS: We prospectively measured systemic, renal vein (RV), inferior vena cava (IVC), and urinary copy number of the mtDNA genes COX3 and ND1 by quantitative-PCR in CEH and ObAAEH patients during constant sodium intake and antihypertensive regimens, and compared them with healthy volunteers (HV) ( n = 23 each). RESULTS: Blood pressure was similarly elevated in CEH and ObAAEH, while glomerular filtration rate (GFR) was higher and age lower in ObAAEH. Urinary (but not plasma) COX3 and ND1 were higher in CEH compared to HV, and further elevated in ObAAEH patients. COX3 and ND1 renal gradients (RV–IVC) were higher in ObAAEH vs. CEH, and their urinary levels directly correlated with GFR. In multivariate analysis, GFR remained the only predictor of elevated urinary COX3 and ND1 levels. CONCLUSIONS: Urinary fragments of the mitochondrial genome are elevated in ObAAEH patients and correlate with glomerular hyperfiltration. A positive gradient across the kidney in ObAAEH suggests selective renal release. These results are consistent with mitochondrial injury that may aggravate renal damage and accelerate hypertension-related morbidity/mortality rates in ObAAEH.